PENGEMBANGAN MEDIA POP UP BOOK BERBASIS PjBL MATERI PENGUKURAN PANJANG DAN BERAT DI SEKOLAH DASAR - Adinda Ayu Puspita Rani; Kunti Dian Ayu Afiani; Deni Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning media in the form of a Pop-Up Book focused on mathematics topics related to the measurement of length and weight. The main objective of this research is to assess the extent to which the Pop-Up Book media meets three key criteria: validity, practicality, and effectiveness in a primary school setting, specifically at SD Muhammadiyah 17 Surabaya. The research method used is a research and development (R&D) approach with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study are 28 third-grade students at SD Muhammadiyah 17, while the object of the research is the Pop-Up Book learning media on length and weight measurement. The instruments used to collect data include questionnaires for content and media experts to assess validity, as well as questionnaires for students and teachers to evaluate practicality, and tests to measure the effectiveness of the media in improving students' understanding. The data were analyzed using a Likert scale ranging from 1 to 5 to evaluate the validity, practicality, and effectiveness of the media. The results of the study showed that the developed Pop-Up Book received very positive feedback. The average validity rating from 3 validators was 84%, which falls into the